Correction to: Psychotic like experiences in healthy adolescents are underpinned by lower fronto-temporal cortical gyrification: a study from the IMAGEN consortium : correction - Maitra, Raka; Horne, Charlotte M; O’Daly, Owen; Papanastasiou, Evangelos; Gaser, Christian; Banaschewski, Tobias; Flor, Herta; Nees, Frauke; Hohmann, Sarah; Millenet, Sabina (Schizophrenia bulletin, 2023)
This is a correction to: Raka Maitra, Charlotte M Horne, Owen O’Daly, Evangelos Papanastasiou, Christian Gaser, IMAGEN list of authors, IMAGEN Consortium, Psychotic Like Experiences in Healthy Adolescents are Underpinned by Lower Fronto-Temporal Cortical Gyrification: a Study from the IMAGEN Consortium, Schizophrenia Bulletin, 2022;, sbac132, https://doi.org/10.1093/schbul/sbac132.In the originally published version of this manuscript, author, Sukhi Shergill, was not properly acknowledged in the PDF and HTML version of the papers. This error has been corrected.
Online veröffentlicht: 17. November 2022
Gesehen am 08.07.2024